Instant Corn Rice Product Development - Hidayat, Khoirul; Mu'tamar, Mohammad Fuad Fauzul; Firmansyah, R Arief; Illahi, Wahyudi (Jurnal Teknik Industri, 2019)
The Madurese consumes corn as the primary source of carbohydrates. However, currently, they are experiencing a shift in consumption from corn to rice. It is caused by the availability of abundant rice. Moreover, another reason is the process of processing corn requires a relatively long time. The purpose of this research is to develop instant Madura corn rice. The method used in this research is the Quality Function Deployment (QFD) method. Based on the House of Quality matrix obtained 16 attributes of consumer needs both in terms of products and packaging. Highest Attributes of the needs of consumers are attributes without preservatives for the product aspect and presenting attributes for the packaging aspect. There are 17 attributes of technical requirements needed to meet the attributes of consumer needs. Highest priorityÂ  The technical requirements are the corn type attribute for the product side and the font-size attribute for the packaging aspect. The results of product comparisons with competitors, Madura corn rice products have advantages in the yellow color attribute. Furthermore, It needs to be improved attributes about the texture a little soft.